2016
DOI: 10.1016/j.ympev.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and evolution of Zfp36l3

Abstract: In most mammals, the Zfp36 gene family consists of three conserved members, with a fourth member, Zfp36l3, present only in rodents. The ZFP36 proteins regulate post-transcriptional gene expression at the level of mRNA stability in organisms from humans to yeasts, and appear to be expressed in all major groups of eukaryotes. In Mus musculus, Zfp36l3 expression is limited to the placenta and yolk sac, and is important for overall fecundity. We sequenced the Zfp36l3 gene from more than 20 representative species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Thus, there are currently 59 and 57 CCCH zinc finger proteins in mice and humans, respectively (TABLE 1). Zfp36l3 is a rodent-specific gene 6 and does not exist in humans. Human ZC3H21 is a pseudogene and not listed in TABLE 1.…”
Section: Ccch Zinc Finger Proteinsmentioning
confidence: 99%
“…Thus, there are currently 59 and 57 CCCH zinc finger proteins in mice and humans, respectively (TABLE 1). Zfp36l3 is a rodent-specific gene 6 and does not exist in humans. Human ZC3H21 is a pseudogene and not listed in TABLE 1.…”
Section: Ccch Zinc Finger Proteinsmentioning
confidence: 99%
“…to the placenta and yolk sac of certain rodents, but not other mammals Frederick et al, 2008;Gingerich et al, 2016). As we show here, its complete deficiency in the mouse leads to significant decreases in the numbers of surviving offspring.…”
Section: Discussionmentioning
confidence: 51%
“…Second, deep sequencing experiments have shown that its mRNA levels are the highest of the three family members found in human placenta (Saben et al, 2014). Finally, Zfp36l1 mRNA is the most highly expressed of the family members in the placentas from the rodent Nannospalax galili, a species very close evolutionarily to the rodents that express ZFP36L3, but which apparently does not express ZFP36L3 in the placenta (Gingerich et al, 2016). Although there are no good cellular models available of human syncytiotrophoblast cells, it might be possible to do specific mRNA knockdown experiments in either human trophoblast or choriocarcinoma cell lines that have been used to model placental transport systems in previous experiments (Ikeda et al, 2011;Lager et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought to have arisen in an ancestor of these species about 25-30 million years ago through a process of retrotransposition involving Zfp36l2 [51]. It is an intronless, imprinted X-chromosome gene whose expression is limited to placenta and yolk sac in the mouse [52].…”
Section: Loss Of Function Mutationsmentioning
confidence: 99%